2004
DOI: 10.1111/j.1748-0361.2004.tb00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress Among Migrant and Seasonal Farmworkers in Rural Southeast North Carolina

Abstract: Findings from the study suggest the availability of social support systems may provide significant insight into developing appropriate health services for migrant and seasonal farmworkers and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 19 publications
6
60
1
Order By: Relevance
“…31,37 Our data suggest that the deportation experience creates an affective reaction that may increase the likelihood that women will engage in high-risk behaviors (e.g., drug use, unprotected sex), as documented elsewhere. [38][39][40][41] Studies with refugees have identified a relationship between depressive symptomatology and cognitive impairment that makes the acculturation process difficult. [42][43][44][45][46][47][48] High-risk behaviors have also been associated with the dissolution of family support networks, homelessness, long-term unemployment and poverty.…”
Section: Discussionmentioning
confidence: 99%
“…31,37 Our data suggest that the deportation experience creates an affective reaction that may increase the likelihood that women will engage in high-risk behaviors (e.g., drug use, unprotected sex), as documented elsewhere. [38][39][40][41] Studies with refugees have identified a relationship between depressive symptomatology and cognitive impairment that makes the acculturation process difficult. [42][43][44][45][46][47][48] High-risk behaviors have also been associated with the dissolution of family support networks, homelessness, long-term unemployment and poverty.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that job concerns were associated with Filipino immigrant workers' adverse health outcomes and that the association was the strongest for the newest immigrants (de Castro, Gee, & Takeuchi, 2008). Migrant farm workers reported concerns related to job insecurity, legal status, language barriers, poor housing conditions, discrimination, and absence from family or friends (Kim-Godwin & Bechtel, 2004;Magana & Hovey, 2003). Studies with Chinese immigrants suggested that, for economic survival, immigrants worked in positions requiring less skill and conveying lower socioeconomic status than positions they had had in their home countries.…”
Section: Job Concernsmentioning
confidence: 98%
“…The literature shows that poverty, immigration status, birthplace, barriers to care (linguistic and structural), discrimination, access to services, lack of services, lack of insurance, work-related stress, stigma, acculturation, rural/urban residency, length of residency, and weakened social support are important risk factors in Hispanic mental health (see, e.g., Cabassa, Zayas, & Hansen, 2006; Escobar et al, 2000; Kim-Godwin & Bechtel, 2004; Lara, Gamboa, Kahramanian, Morales, & Bautista, 2005; Roberts, 1980; Rohrer, Borders, & Blanton, 2005; Vega, Alderete, Kolody, & Aguilar-Gaxiola, 1998; Vega, Kolody, Aguilar-Gaxiola, & Catalano, 1999; Vega, Kolody, Hough, & Figueroa, 1987; Vega & Lopez, 2001; World Health Organization World Mental Health Survey Consortium, 2004). Of these mental health risk factors among Hispanics reported in the literature, birthplace, acculturation, and length of residency are within the scope of our survey and are examined more closely here.…”
Section: Background and Literature Reviewmentioning
confidence: 99%